Grenzüberschreitende Daseinsvorsorge in der Euregio Maas-Rhein. Was kann die Euroregion Pro Europa Viadrina lernen? - Unfried, Martin (Grenzüberschreitende Daseinsvorsorge. Stand und Perspektiven in europäischen Verflechtungsräumen, 2025)
Abstract: „Die euregionalen Partner in der Euregio Maas-Rhein, am Dreiländereck Deutschland/Niederlande/Belgien, haben in den letzten Jahrzehnten viel Erfahrung gesammelt beim Aufbau von Netzwerken im Bereich der öffentlichen Dienstleistungen. Der Artikel stellt wesentliche Netzwerke vor, wobei ausführlicher eingegangen wird auf die Entwicklungen im Bereich der Notfallrettung und der Gesundheitsversorgung, des öffentlichen Nahverkehrs und der Wohnungsmarktpolitik.“
Keywords: Euregio Maas-Rhein; Medizinische Versorgung; Rettungswesen; Wohnungsmarkt; Wohnungspolitik; Öffentlicher Personennahverkehr

Euregio Carolus Magnus. Grenzen in Fluss. Wissenswertes, Historisches, Kurioses rund um das Städtedreieck Maastricht - Aachen - Lüttich - Kamermans, Johanna (Verlag Mainz, 2004)
Keywords: Aachen (Region); Euregio Maas-Rhein; Lüttich; Maastricht

The Maas-Rhine Euroregion. A Laboratory for European Integration? - Knippenberg, Hans (Geopolitics, 2004)
„The transborder and trilingual Maas–Rhine Euroregion is often presented as a laboratory for European integration. The authorities in the region promote the image of a region that has ‘always’ been a unity, but which is divided by artificial boundaries – ‘scars of history’ – as a result of power politics. In this essay this image is confronted with the reality of the cross-border interactions and identities of the people involved. This confrontation leads to the conclusion that although there is political, economic and cultural cooperation in the region, the region is not at all politically, economically and culturally integrated. The national border as a physical barrier may have been removed, but the economic, social, juridical and cultural barriers are still there. The unification and integration of the citizens living in the region is being impeded by conflicting national systems of law and regulations, by communication and information media focused on national issues, by nationally oriented infrastructure, and especially by strongly different national cultures and identities. The consequences for European integration in general are analysed by comparing this regional integration with the national integration and nation-building policies of the past.“
Keywords: Euregio Maas-Rhein; Europäische Integration; Grenzüberschreitende Kooperation

Historische interacties in de Euregio Maas-Rijn. Migratiestromen in een grensgebied - Korres, Achim (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 2002)
Keywords: Arbeitsmigration; Euregio Maas-Rhein; Grenzarbeitnehmer

Wisselende perspectieven van grensligging in de geschiedenis van de euregio Maas-Rijn - Jansen, Johannes C. G. M. (Studies over de sociaal-economische geschiedenis van Limburg/Jaarboek van het Sociaal Historisch Centrum voor Limburg, 1997)
Keywords: Euregio Maas-Rhein; Grenzüberschreitende Kooperation